High-directivity genetic microstrip patch antenna. Issue 3 (2nd July 2016) - Jayasinghe, J.M.J.W.; Anguera, J.; Uduwawala, D.N.; Andújar, A.
Abstract : A high-directivity microstrip patch antenna (MPA) is attractive, since a narrow broadside beam can be obtained without using an array of antennas. Therefore, the solution becomes simpler as there is no complex feeding network as in an array. In this sense, this letter presents a single-element high-directivity MPA, which can substitute a 2 × 2 array operating in the fundamental mode. The novel MPA is designed by using genetic algorithms to fit the patch inside an area of 1 λ × 1 λ, resulting in a directivity of 13.2 dBi in the broadside direction. The MPA is fabricated and the simulation results are in good agreement with the measurements. The element is attractive for antennas with moderate directivity as those used in hot-spots.